ANALISIS FAKTOR PENYEBAB ANAK PUTUS SEKOLAH PADA SEKOLAH DASAR NEGERI TUKBUR DESA LAKATULI KECAMATAN MATARU - Tofilus Ataruli; Triznawasti Y. Daik (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to determine the causes of school dropout and the efforts made to address this problem at Tukbur Public Elementary School, Lakatuli Village, Mataru District. This situation is a concern because education is a right for every child that must be fulfilled and is an obligation for every Indonesian citizen. The subjects of this study were the principal, village head, parents of dropouts, and the children themselves. Data collected in this study were interviews and documentation, then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the study at Tukbur Public Elementary School, Lakatuli Village, Mataru District, indicate that factors causing children to drop out of school consist of internal and external factors. Internal factors include health conditions, low motivation to learn, lack of interest in learning, trauma due to school experiences, and peer influence. External factors include family economic conditions, the death of a parent, lack of family attention, the residential environment, and administrative constraints. Efforts to address the issue of school dropouts can involve collaboration between parents, schools, village governments, and the community through motivational campaigns and outreach on the importance of education.